Implementation Of Regional Regulation Number 6 Of 2020 Concerning the Implementation of Public Information Disclosure in the Berbas Tengah Village - A, Sumarni; Kusuma , Aji Ratna; Rande , Santi; Patel, Manthan (Universitas Muhammadiyah Makassar, 2025)
This study is motivated by the persistent gap between Indonesia’s increasingly robust legal framework on open government and the uneven realization of public information disclosure at the local level, where transparency practices remain fragmented and often exclusionary. The research aims to examine how public information disclosure is operationalized in Berbas Tengah Urban Village, with particular emphasis on the interplay between regulatory mandates, institutional capacity, information technology, and community participation under Regional Regulation Number 6 of 2020. A descriptive qualitative design was employed through a single-case study, combining in-depth interviews with village officials and community members, participatory observation of information service practices, and document analysis of regulatory instruments, planning documents, and activity reports; the data were analyzed thematically using a good governance framework that foregrounds transparency, accountability, and participation. The findings show that effective disclosure is driven by institutional commitment, the establishment of an information management structure, and the strategic use of digital platforms, while it is constrained by limited human resources, infrastructural gaps, and low digital as well as legal literacy. Community participation emerges as both a driver and a barometer of disclosure—functioning as social control and performance evaluation—yet remains skewed toward more educated and digitally literate groups, thereby reproducing digital and social inequalities. The study concludes that public information disclosure is not merely a procedural or administrative requirement but a governance practice that can enhance responsiveness, trust, and accountability at the village level when it is adequately supported. The novelty of this research lies in its integrated analysis of digital transparency and civic participation within a subnational urban context, revealing a non-linear relationship between technology access, participation levels, and governance quality. Empirically, the study advances the literature on local governance and transparency in the Global South and, in practical terms, offers insights for policymakers to design more inclusive, technology-enabled information regimes that reduce digital divides and strengthen grassroots democratic governance